Comparison of Mast Cells and Inflammatory Cells within Periapical Lesions and Comparison of Degranulated Mast Cells Between Fibrous and Inflamed Area in Radicular Cysts: An Immunohistochemical Study - Shiromany, Aseem (J Clin Diagn Res, 2014)
Objective: The role of mast cells as the key effector of allergic inflammation, anaphylactic inflammatory reactions and in the pathogenesis of chronic inflammation, is well-known. The present study is adopted to compare mast cells and inflammatory cells within periapical granuloma and cysts and localize the mast cells and quantify their number in the periapical cysts so as to propose a role of mast cells in the pathogenesis of this lesion. Materials and Methods: Biopsy specimens of 30 periapical lesions were stained with hematoxylin–eosin, and immunohistochemical Mast Cell Tryptase from Bio SB (IHC detection system kit) antibody. The tryptase positive mast cells and mononuclear inflammatory cells were counted in 10 consecutive high power fields (100X) using the binocular microscope from Motic attached to a computer with Motic Advanced Images 3.2 software. Results: Comparative microscopic analysis indicated that periapical cyst shows more percentage of mast cells and less percentage of inflammatory cell than periapical granuloma (comparison of mean and standard deviation of total number of mast cells and inflammatory cells, mast cells 3.15±1.39 in the granuloma group and 4.43±1.91in the cyst group, inflammatory cells, 67.11±1.2 in the granuloma group and 52.66±0.8 in the cyst group). Numerous degranulated mast cells were observed in the fibrous wall than the inflammatory infiltrate of the periapical cysts. The mean and standard deviation of degranulated mast cells between the inflammatory and fibrous zone within the cyst group, being 0.95±1.10 and1.68±1.34 respectively. The values varied significantly between the two zones. Conclusion: The number of inflammatory cells in the cyst group is less than periapical granuloma and total number of mast cells in the cyst group is more as compared to periapical granuloma. The degranulated cells were quantified and they were higher in the fibrous area of the cysts than the inflammatory zone. This study could support the fact that the various mediators released on degranulation play a role in the connective tissue remodeling, chronicity and expansion of the periapical lesion.